GAMIFICATION IN ISLAMIC RELIGIOUS EDUCATION: STRENGTHENING ISLAMIC CHARACTER BUILDING THROUGH LEARNING THE PROPHET'S SIRAH AT AISYIYAH ELEMENTARY SCHOOL IN CINDOGO, BONDOWOSO - Nabilah, Maryam; Sutriani; Dina Mardiana (As-Sulthan Journal of Education, 2025)
This qualitative case study examines the application of gamification in Islamic Religious Education (PAI) at Aisyiyah Cindogo Bondowoso Elementary School, focusing on the Sirah Nabawiyah material to strengthen character building and learning motivation of elementary school students. Using the Sygma Daya Insani package, the weekly 90-minute Sirah Nabawiyah Club session incorporates game elements—such as points, badges, quests, and collaborative challenges—into three stages: a reflective opening, game-based Exploration, and character dialogue. Data were obtained through participant observation, in-depth interviews with seven informants, document analysis, and focus group discussions. These data were then analyzed thematically with triangulation to ensure validity. The results show significant improvements in five dimensions of Islamic character—self-confidence, caring, honesty, discipline, and empathy—as evidenced by active participation, honest reporting, and positive behavioral changes at home. Gamification transforms passive memorization into an immersive and meaningful learning experience, connecting the exemplary values ​​of the Prophet Muhammad with real-life practices. This research confirms the role of gamification as a differentiated pedagogy that is inclusive and relevant to the needs of 21st-century Islamic Education (PAI). Further research is recommended to develop open-source and low-tech gamification models for broader replication.